DEVELOPMENT OF PROBLEM-BASED LEARNING INSTRUCTIONAL DESIGN TO IMPROVE THE PROBLEM-SOLVING ABILITY OF SMA NEGERI 3 LAMONGAN STUDENTS - Layliah, Ananda Faridatul; Machsunah, Yayuk Chayatun (STKIP PGRI Situbondo, 2024)
Learning design is essential in improving the quality of learning and students' learning experience. However, many universities (especially in Information Technology) have not developed a structured learning design, so the learning process becomes ineffective. The PBL approach is used because it encourages students to actively solve real problems relevant to the learning material, which will develop problem-solving skills, critical thinking, collaboration, and creativity. This approach is supported by constructivism and social cognitive theories, which emphasize the active role of students in constructing their knowledge through interaction with learning content and social interaction. The results of the limited trial showed a significant increase in post-test scores compared to the pre-test, supporting the concept that active learning, as implemented in the PBL module, can improve student understanding. Developing and testing this module reflects a systematic and sustainable approach to designing effective instruction, potentially enhancing the quality of education in Indonesia.